Dynamics of fertilizer application and nutrition loss on agricultural land in Belarus - Lamanos, Mikhail; Lamanos, Volha (Journal of the Belarusian State University. Ecology, 2023)
The article presents the results of a comparative analysis of the statistical data of the National Statistical Committee of the Republic of Belarus for a five-year period (2017–2021) on the application of mineral fertilizers on the agricultural lands of Belarus, calculated and presented the losses of the main nutrients (nitrogen, phosphorus, potassium) during their application. The calculation of the productivity of agricultural crops was made, on the basis of which the indicators of the removal of nutrients with the harvest were established. The calculation of the productivity of agricultural crops was made, on the basis of which the indicators of the removal of nutrients with the harvest were established. The difference between the incoming and outgoing parts of the fertilizer elements was determined to assess the effect of applied mineral fertilizers on the environment. According to the presented data, there is a decrease in the application of mineral fertilizers compared to the previous period (2012–2016) by 59 kg/ha a.i. Calculation of the structure of nitrogen flowrate items on average in the republic for 2017–2021 shows that a significant part of nitrogen (72 % of the total amount) is used to form crop yields, and the remaining amount is gaseous losses (21 %), losses from leaching (6 %) and soil erosion (1 %). Almost all of the phosphorus applied with fertilizers is used by crops to form crops, and only a small part of it is lost as a result of erosion processes (0.1–0.4 kg/ha). Potassium losses are 10 %, of which 9 % is lost as a result of leaching. Strict observance of the conditions of transportation, storage, mixing of fertilizers, optimization of the use of mineral fertilizers based on scientifically based recommendations will ensure their efficient use and thus significantly reduce the risks of negative effect of fertilizers on the environment. Strict adherenceto technological recommendations for their application will help prevent ecosystem imbalance.
Keywords: mineral fertilizers; gaseous losses; leaching; erosive losses; ecology; environment